WORLD BANK AND DECENTRALIZED CLIMATE FINANCE: IMPLEMENTATION GAPS IN LAMU, KENYA - Fatuma Bwanaheri Abdulrahman; Dudy Heryadi; Siti Aliyuna Pratisti (Intermestic: Journal of International Studies, 2026)
This paper analyses the World Bank initiatives in promoting its role in decentralizing climate finance through the Financing Locally-Led Climate Action (FLLoCA) and the Kenya Climate-Smart Agriculture Project (KCSAP) in Lamu County, Kenya. A qualitative case study is used to examine the substantial tension between the Bank's perception of its institutional function, its actual bureaucratic performance, and the pressing demands, through the intersection of Function of Role Theory and Climate Resilience Theory. A significant implementation gap is revealed from the empirical findings, highlighting that the creation of the local ward committees in the projects purportedly regularizes climate governance. However, the strict procurement regulations provided by the Bank, systemic delays in the release of funds, and strict environmental standards have compromised local sovereignty. Misplaced expectations are frequently encounters through these efforts and the occurrence of elite capture, hindering marginalized groups from cultivating genuine and transformative resilience. This paper concludes that the international development finances must abandon rigid technological imposition in favour of adaptable funding models and genuinely integrate local survival knowledge to thrive in extremely fragile socio-ecological zones.